We know that the standard form is
ax + by = c
So, let's solve this problem to get correct answer
y = -2/3x + 4 { multiplying each term by 3 }
3y = -2x + 12 { according to the standard form equation our x variable should be on other side so let move that} { adding 2x on both sides }
2x + 3y = 12
Hence the correct option is B.
If you want to check your answer resolve your answer and see if you get the same quotient.
2x + 3y = 12
3y = -2x + 12 { subtracting both sides by -2x }
y = -2/3x + 12/3 {dividing both sides by 3 }
y = -2/3x + 4 { same as the quotient }
Hence proved.